Peripheral refraction and retinal contour in stable and progressive myopia - Ribeiro, Miguel Faria (2013)
Purpose. To compare the patterns of relative peripheral astigmatic refraction (tangential and sagittal power errors) and eccentric eye length between progressing and stable young-adult myopes. Methods. Sixty-two right eyes of 62 white patients participated in the study, of which 30 were nonprogressing myopes (NP group) for the last 2 years and 32 were progressing myopes (P group). Groups were matched for mean spherical refraction, axial length, and age. Peripheral refraction and eye length were measured along the horizontal meridian up to 35 and 30 degrees of eccentricity, respectively. Results. There were statistically significant differences between groups (p G 0.001) in the nasal retina for the astigmatic components of peripheral refraction. The P group presented a hyperopic relative sagittal focus at 35 degrees in the nasal retina of +1.00 T 0.83 diopters, as per comparison with a myopic relative sagittal focus of j0.10 T 0.98 diopters observed in the NP group (p G 0.001). Retinal contour in the P group had a steeper shape in the nasal region than that in the NP group (t test, p = 0.001). An inverse correlation was found (r = j0.775; p G 0.001) between retinal contour and peripheral refraction. Thus, steeper retinas presented a more hyperopic trend in the periphery. Conclusions. Stable and progressing myopes of matched age, axial length, and central refraction showed significantly different characteristics in their peripheral retinal shape and astigmatic components of tangential and sagittal power errors. The present findings may help explain the mechanisms that regulate ocular growth in humans.